Aluminium‐Catalysed Oxazolidinone Synthesis and their Conversion into Functional Non‐Symmetrical Ureas. Issue 13 (18th August 2015) - Laserna, Victor; Guo, Wusheng; Kleij, Arjan W.
Abstract An efficient and practical aluminium‐catalysed approach towards a range of functional oxazolidinones is reported. The method is based on cheap and readily available starting materials including terminal and internal (bicyclic) epoxides and phenyl carbamate. The oxazolidinones serve as highly useful synthons for the high yield preparation of non‐symmetrical ureas by nucleophilic ring‐opening affording the targeted urea compounds with excellent functional group diversity, high regioselectivity and isolated yields up to >99%.